(untitled) - Messadié, Gerald (New York, 1991)
Dealing with inventions before 1850, this is one of a series of reference books covering a range of popular subjects, and written and presented in a manner which is designed to appeal to both students and general readers.
Keywords: Inventions,Sáng chế; History,Lịch sử